Synthesis and Characterization of Photoactive S-Tio2 from Tioso4 Precursor Using an Integrated Sol-Gel and Solvothermal Method at Low Temperatures (2018)
Photoactive S-titanium dioxides (S-TiO2) were synthesized from TiOSO4 as only Ti and S precursor using an integrated sol-gel and solvothermal method at low temperatures (200 °C - 250 °C). The effect of the synthesis conditions (molar ratios of water/TiOSO4 and solvent (ethanol)/TiOSO4 as well as temperature, < 250 °C) of the applied method in the properties and the photoactivity of the synthesized materials was evaluated through Box-Behnken experimental design. The prepared photocatalysts were characterized by X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray fluorescence (XRF), attenuated total reflectance - Fourier transform infrared spectroscopy (ATR-FTIR), ultraviolet - visible diffuse reflectance spectroscopy (UV/vis-DRS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), porosity and BET surface area analysis. The photocatalytic activities of the synthesized S-TiO2 materials were determined by the photodegradation of formic acid. Results indicated that the integrated sol-gel and solvothermal method at low temperatures led to obtain mesoporous, crystalline and photoactive S-TiO2 materials, crystallized as anatase phase with UV and visible light absorption for all synthesis conditions. All synthesized S-TiO2 materials showed high activity in formic acid photodegradation, which was associated on their degrees of crystallinity, particle sizes and sulfur contents, being higher in the materials synthesized with the temperature of 250 °C. Material synthesized with molar ratio water/TiOSO4 of 4.0, molar ratio ethanol/TiOSO4 of 15 and T = 250 °C, showed the highest photocatalytic activity, a crystallite size of 42.34 nm, surface area of 35.77 m2/g, sulfur content of 0.818 wt %, high UV and visible radiation absorption and band gap of 3.03. © 2017.